The Importance of the Discussion About the Legal Nature of Possession - Igor V. Popov; Veronica V. Butina (Сибирское юридическое обозрение, 2016)
The article considers different views on the legal nature of possession, defines the meaning of the discussion on this matter. A historical and comparative analysis of the problems of possession protection in Russia and in foreign countries is carried out. Special attention is paid to the question of indirect (double) possession. After analyzing upcoming changes in the legal regulation of property relations, the Authors express their opinion on expediency of introduction of the institution of possessory protection in the modern Russian civil legislation.